PENYELIDIKAN TINDAK PIDANA PERDAGANGAN ORANG OLEH DIREKTORAT INTELKAM POLDA RIAU - Ikhsan Adi Nugraha; Syaifullah Yophi Adriyanto; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
AbstractCrime of Trafficking in Persons is a dangerous crime and increasing fromyear to year, which can affect the life of the nation and state of Indonesia which isthe successor to the ideals of the nation and the state. Victims of the Crime ofTrafficking is not looking at anyone either women, children, students,. Traffickingin persons is a crime is a form of crime Extraordinary Crime and many use themodus operandi vary and the actors are very organized, as players move around aplace to fool the police. In the eradication of the Trafficking in Persons requiredperformance of the police in finding the perpetrators of these acts of humantrafficking, which starts from the investigation stage to the stage of documentanalysis.In accordance with the above description, the authors are interested indoing research with the title of the Crime of Trafficking in Persons InvestigationBy Intelkam Riau Police Directorate. In this thesis the following aims is to findout how the implementation of the criminal investigation by the Directorate ofTrade this guy Intelkam Riau Police, then to find out the barriers in theimplementation of human trafficking investigations conducted by the DirectorateIntelkam Riau Police, and the latter aims to determine the effort made inovercoming obstacles in the implementation of human trafficking investigation bythe Directorate Intelkam Riau Police.In writing this paper the author uses research methods, types ofsociological research. The sociological research is research that is done byidentifying the effectiveness of the law and how the law applies in society.Descriptive nature of the research, aims to provide a clear and detailed picture ofthe implementation of human trafficking investigation by the Directorate IntelkamRiau Police. The results of research conducted using qualitative analysis anddeductive methods, the decomposition problem of a general nature that is specificto the problem.From the results of this study concluded that in the investigation of humantrafficking is not running as it should be for not doing the investigation stages thathave been regulated by the Chief of Police of the Republic of Indonesia No. 14 of2012, the lack of personnel and experience of investigators in the investigation ofhuman trafficking this, and the need for cooperation with the community incombating human trafficking, lack of facilities and infrastructure that are neededas operational vehicles that become obstacles in the implementation of criminalinvestigations by the Directorate of Trade Intelkam Riau Police.Keywords: Investigations-Crime-Trafficking in Persons Law Enforcement